2002
DOI: 10.1038/sj.bjc.6600451
|View full text |Cite|
|
Sign up to set email alerts
|

The epidemiology of conjunctival squamous cell carcinoma in Uganda

Abstract: As part of a larger investigation of cancer in Uganda, we conducted a case -control study of conjunctival squamous cell carcinoma in adults presenting at hospitals in Kampala. Participants were interviewed about social and lifestyle factors and had blood tested for antibodies to HIV, . The odds of each factor among 60 people with conjunctival cancer was compared to that among 1214 controls with other cancer sites or types, using odds ratios, estimated with unconditional logistic regression. Conjunctival cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 40 publications
5
82
2
1
Order By: Relevance
“…Although rare in Europe and USA, conjunctival neoplasia has been reported to be relatively common in regions of sub-Saharan Africa since the 1960s (Templeton, 1973). An emerging miniepidemic of conjunctival tumours has been described in Rwanda, Uganda and Tanzania in association with the epidemic of HIV infection since the 1980s (AteenyiAgaba, 1995;Waddell et al, 1996;Newton et al, 2002). The spread of HIV in Uganda, indeed, probably accounts for much of the approximately eight-fold increase in the incidence of conjunctival carcinoma observed during the last 20 years (Wabinga et al, 2000).…”
mentioning
confidence: 99%
“…Although rare in Europe and USA, conjunctival neoplasia has been reported to be relatively common in regions of sub-Saharan Africa since the 1960s (Templeton, 1973). An emerging miniepidemic of conjunctival tumours has been described in Rwanda, Uganda and Tanzania in association with the epidemic of HIV infection since the 1980s (AteenyiAgaba, 1995;Waddell et al, 1996;Newton et al, 2002). The spread of HIV in Uganda, indeed, probably accounts for much of the approximately eight-fold increase in the incidence of conjunctival carcinoma observed during the last 20 years (Wabinga et al, 2000).…”
mentioning
confidence: 99%
“…13,18 However, these studies have observed a novel association of HIV infection with conjunctival cancer. 19 Cohort studies have not been used to study risk of cancer among persons with HIV/AIDS in Africa.…”
mentioning
confidence: 99%
“…HPVs are most commonly associated with cervical cancer, although, it is now known that many cancers are induced by HPV, including penile, anal, oral, and conjunctival cancers (Durst et al, 1983;Koutsky, 1997;Newton et al, 2002;Syrjanen, 2003;Waddell et al, 1996). High-risk HPVs have also been implicated recently in ~30% of oral cancers (Gillison et al, 2000).…”
Section: A Types Of Hpv-induced Cancersmentioning
confidence: 99%
“…HPV infections of the conjunctiva of the eye are more common than previously appreciated, although resulting HPV-induced tumors of the conjunctiva are very rare (Mincione et al, 1992(Mincione et al, , 2006Reszec and Sulkowski, 2005;Tabrizi et al, 1997;Waddell et al, 2003). Though the incidence of eye or eye-orbit tumors in the United States is extremely low (<1/100,000) (Gloeckler Ries et al, 2003), in African countries, conjunctival tumors are more common and are undoubtedly influenced by nutrition, additional disease burdens, but most obviously by the relatively high impact of HIV in Africa (Ateenyi- Agaba et al, 2006;Frisch et al, 2000;Goedert, 2000;Newton et al, 2002;Waddell et al, 1996Waddell et al, , 2003.…”
Section: A Types Of Hpv-induced Cancersmentioning
confidence: 99%